Melt electrowritten medium chain length polyhydroxyalkanoate cardiac patches for Post-MI cardiac regeneration - Majid, Qasim A.; Pandey, Pragati; Bellahcene, Mohamed; Grigsby, Christopher L.; Stevens, Molly M.; Talman, Virpi; Stuckey, Daniel J.; Harding, Sian E.; Roy, Ipsita; Foldes, Gabor (ELSEVIER, 2026)
Human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs) hold promise in averting the development of heart failure with reduced ejection fraction (HFrEF) following myocardial infarction (MI) by potentially regenerating the infarcted myocardium and restoring left ventricular contractility. However, challenges remain regarding the structural and functional maturation states of these cells, as well as their retention and integration into the myocardium. Here, we developed a novel three-dimensional cardiac patch and evaluated its potential to instigate cardiac regeneration. For the first time, melt electrowriting (MEW) was utilised to fabricate reproducible, structurally anisotropic, and handleable scaffolds from high molecular weight, medium chain-length polyhydroxyalkanoates (MCL-PHAs). These MEW-PHA scaffolds maintained hPSC-CMs, facilitating their rapid structural maturation and functional improvement in vitro. Different combinations of hPSC-derived cardiovascular cells were seeded onto the MEW-PHA scaffolds and stacked to create synchronously beating, multi-scaffold cardiac patches. These were well-accepted in a murine MI model without capsule formation. Notably, cardiac patches containing hPSC-derived cardiac microvascular-like endothelial cells (hPSC-CMVECs) initiated vascular regeneration within the infarcted myocardium. This novel advancement enabled the reproducible fabrication of high molecular weight MCL-PHA-based MEW cardiac patches that matured hPSC-CMs and promoted vascular regeneration, offering potential for future improvement in post-MI cardiac function through enhanced hPSC-CM retention.